31 Perioperative medicine for older people undergoing surgery (POPS) fellowship: developing leaders in geriatric perioperative medicine. (3rd November 2019) - Lal, Rajni; Jasper, Emily; Mainwaring, Cathryn; Partridge, Judith; Dhesi, Jugdeep
Abstract : Background: Perioperative medicine (POM) for older people is an emerging geriatric subspecialty where effective leadership is essential to support national growth. POPS is an evidenced-based, geriatrician-led, multidisciplinary team, providing comprehensive geriatric assessment(CGA) for older patients undergoing elective and emergency surgery. There is heterogeneity observed in the UK, with only 53% of trusts providing POPS services in 2018. 1 UK surveys demonstrate current provision does not meet demand, meaning developing leaders in POM is vital for scaling POPS services. Method: The GSTT POPS fellowship was developed in 2012 to provide Specialist Registrars the opportunity to spend a year under the supervision of POM geriatricians. Fellows develop experience in CGA before elective surgery and inpatient care for all older surgical patients. The curriculum outlines expected knowledge, behaviours and opportunities available. Leadership skills are developed through independent work, junior supervision, research and mentorship from geriatricians. Results: 10 trainees have completed the fellowship, with 6 now working POPS Consultants. Achievements include; 16 quality improvement projects, 5 publications, 5 awarded grants, a Darzi fellowship and representation on national bodies (eg.NELA). The wider impact is seen through UK POPS expansion and improved outcomes for older patients in NELA. 1, 2 Conclusion: In the context of workforce shortages, difficulties in geriatrician recruitment requires service flexibility. This led to the development of a POPS fellowship, now producing future POM leaders. References: Joughin A, Partridge J, O'Halloran T, et al. Where are we now in perioperative medicine? Results from a repeated UK survey of geriatric medicine delivered services for older people. Age Ageing 2019;48:458–462. Fourth Patient Report - National Emergency Laparotomy Audit(NELA). Available from:http://www.nela.org.uk/Fourth-Patient-Audit-Report[Accessed; 2019, May 24]